Effectiveness of explosive sprint and pedaling exercises for physical fitness assessment of throwers - Takanashi, Yuta; Kohmura, Yoshimitsu; Aoki, Kazuhiro (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The reliability of the 30-m sprint and bicycle ergometer tests, which are widely used as an indicator of the explosive muscle capabilities of the leg, has not been studied for the physical fitness assessment of throwers. Aim of Study. This study aimed to clarify whether the sprint and bicycle ergometer tests at short operating times are useful for assessing the competitive performance in the throwing competition. Material and Methods. For 11 male university students, the highest rotation speed (1, 2, 3 s each) was measured at three different loads during a 10-yd running time and bicycle ergometer test (1, 2, 3 s each). The relationship between the measured value and the competitive force (IAAF score) was examined. Results. The results can be summarized as follows: 1) no significant correlation was found between the 10-yd sprint time and athletic performance. 2) A positive correlation between the body mass and the number of revolutions was found so that weight positively affects the maximum rotational speed. 3) A positive correlations were found between the maximum numbers of revolutions at 3 s for each loading condition. Conclusion. These results suggest that (1) the sprint test is unsuitable for throwers, and (2) the maximum pedaling speed for a short period (1.0-2.0 s) with a relatively high load (5.0 kgf) is useful.
Keywords: 30-m sprint test; bicycle ergometer; physical fitness assessment; throwers